Sobre a natureza e os sábios hindus: uma leitura de a Vida de Apolônio de Tiana de Filóstrato - Nathalia Thomazella (2018)
This study purposes a reading and an analysis of the books II and III of Philostratus Life of Apollonius of Tyana, which describe the Apollonius travel to India. Mainly, we focus on this exotic nature and on the sages which the character had contact in that land. In the chapters, we present and discuss some controversies that surround the work itself, but also itsprotagonist. The selected corpus highlights sections that value the studied topics in this research, which enables a rereading not only of its character, but also the way that India was postrayed by the ancient Greeks.